Efforts To Improve Students Ability To Identify Persuasive Speech Ideas To Use Learning Methods In Classroom Teachers IX SMP Negeri 4 Lolofitu Moi Study - Agusman Waruwu (UMSU, 2021)
Language skills are a process in order to convey ideas, messages, attitudes, and opinions to readers using symbols or language symbols. One of the materials that can support the success of language skills is through persuasive speech. Persuasive speech is a type of speech delivered with the aim of influencing the listener, persuading so that they are interested in what is being said.The purpose of this study was to improve the students' ability to identify ideas of persuasive speech text by applying the Peer Tutor learning method for class IX students of SMP Negeri 4 LölöfituMoi Learning Year 2020/2021. The subjects of this study were 24 students of SMP Negeri 4 Lölöfitu Moi class IX-1 semester I. This study uses a Classroom Action Research method with the implementation procedure are (1) planning, (2) action, (3) observation, (4) reflection.The results of the study using the Peer Tutor learning method showed that there was an increase in students' skills in identifying persuasive speech text ideas. This can be seen in the research findings of each cycle, namely cycle I with the average score achieved by students of 56.71 with the lowest score of 35 and the highest score of 70.While in the second cycle there was an increase with the average score obtained by students of 83.59. with the lowest score of 75 and the highest score of 95.Based on the results of this study, it can be concluded that using the Peer Tutor learning method can improve students' ability to identify persuasive speech text ideas and students are more active so that learning is more meaningful. With these conclusions, the recommended suggestions are (1) For Indonesian language teachers at SMP Negeri 4 Lölöfitu Moi to use the Peer Tutor learning method because researchers have conducted research and are proven to improve students' ability to analyze persuasive speech text ideas; (2) For future researchers, so that this research can be carried out even better, including in designing and modifying learning methods that can actually improve the learning process.